Process-Oriented Guided Inquiry Learning and Students' Mathematical Reasoning Ability in Indonesia: A Systematic Literature Review and Meta-Analysis - Nurtamam, Mohammad Edy; Budayasa, I Ketut; Lukito, Agung (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study analyzes the effectiveness of the Process-Oriented Guided Inquiry Learning (POGIL) model in enhancing the mathematical reasoning ability of students in Indonesia. A systematic literature review and meta-analysis approach was employed. The inclusion criteria required data to be sourced from international journals and proceedings indexed in the Science and Technology Index (SINTA), Scopus, and Web of Science. Research data were collected from databases such as Google Scholar, ScienceDirect, Mendeley, Wiley, Springer, and ERIC. Studies included in the analysis were published between 2020 and 2024, focused on the POGIL model and students' mathematical reasoning ability, and provided complete data for effect size calculation. Keywords used for data searches included "Process Guided Inquiry Learning," "Student Mathematical Reasoning," "Implementation of Process Guided Inquiry Learning," and "Effect of Process-Oriented Guided Inquiry Learning on Students' Mathematical Reasoning Ability." Data analysis was conducted using JSAP software version 0.8.5. The findings, based on the analysis of twenty-five effect sizes, indicate that POGIL is highly effective in enhancing students' mathematical reasoning ability in Indonesia. The summary effect size was 1.14, with a p-value less than 0.001 and a confidence interval ranging from 0.512 to 1.35, which is categorized as a very high effect size. Students taught using the POGIL approach demonstrated significantly improved mathematical reasoning skills compared to those taught with conventional methods. This improvement was particularly evident in their ability to analyze mathematical problems, construct logical arguments, and evaluate alternative solutions.